#TITLE_ALTERNATIVE# - Ratnaningsih, Enny
Abstract: Nickel(II) and cobalt(II) are nearly similar in chemical properties. Both can be found in mineral ores, or in any analytically produced mixture. The amount found is usually very small. Special chemical methods may be required to analyze both of them simultaneously. Polarographic analysis using various supporting electrolytes show the existence of two waves which lie very close one to each other. Differential pulse polarographic method is recommended to distinguish between these two waves. It has been found that the addition of DMG will incre ase the diffusion current and also the sensitivity of the method used. Experiments show that in a 0.1 M NH4OH/NH4C1 supporting electrolyte the addition of 6 X 10-4% DMG will increase the diffusion current for a 1 ppm solution of nickel(II) 4 - 5 times, and for a 1 ppm solution of cobalt(II) 3 - 4 times. In a 0,1 M NH4OH/NH4tartrate supporting electrolyte for the same amount of nickel(II) and cobalt(II), the in-crease are 2 - 4 times and 1.3 times respectively. The experiments show also that the amount of DMG used is not unlimited.